1982
DOI: 10.1111/j.1432-1033.1982.tb06815.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Metabolism and Excretion of Orally and Intravenously Administered, Double‐Labeled N‐GIycoloylneuraminic Acid and Single‐Labeled 2‐Deoxy‐2,3–dehydro‐N‐acetylneuraminic Acid in Mouse and Rat

Abstract: N-Glycoloyl-~-[2-' 4C,9-3H]neuraminic acid enzymically prepared from sodium 12-l 4C]pyruvate and Nglycoloyl-~-[6-~H]mannosamine by N-acetylneuraminate lyase in 52 % yield was orally administered to 20-day-old fasted mice. In the course of 6 h 98 "/, of the total radioactivity belonging to the originally administered N-glycoloylneuraminic acid was resorbed from the intestine and appeared in the urine. 6 h after application total 0.7 % of the 3H and 0.5 % of the I4C radioactivity were recovered in blood, liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…Biochemical data showed that a large part of administered radioactive NeuNAc was excreted in a short time (8,23,24). Approximately 90% of NeuNAc was found in the urine between 10 min and 1 hr after intravenous injection (8) and only a small per cent of the applied radioactivity was left in the blood, liver, spleen, kidney and brain at 4 hr after injection (23,24). In our observations, only the kidney, distal portion of small intestine and urine showed substantial radioactivity until 3 hr after injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical data showed that a large part of administered radioactive NeuNAc was excreted in a short time (8,23,24). Approximately 90% of NeuNAc was found in the urine between 10 min and 1 hr after intravenous injection (8) and only a small per cent of the applied radioactivity was left in the blood, liver, spleen, kidney and brain at 4 hr after injection (23,24). In our observations, only the kidney, distal portion of small intestine and urine showed substantial radioactivity until 3 hr after injection.…”
Section: Discussionmentioning
confidence: 99%
“…NeuNAc is a terminal sugar in many glycoconjugates (23), but the previous investigations of NeuNAc metabolism are limited to only a few tissues and organs (10,13,23,24,29,40,41), and there is no study on the tissue distribution of this compound. Whole-body autoradiography developed by Ullberg (36) makes it possible to examine and compare the radioactivities of many organs and tissues under identical conditions.…”
mentioning
confidence: 99%
“…The lack of in vivo activity for FANA led to the generally accepted belief that potent synthetic analogues such as DANA would not have in vivo activity. In addition, subsequent work demonstrated that sialic acid analogues were rapidly excreted (Nohle et al, 1982), leading to the notion that DANA (Neu5Ac2en) analogues would not have potential clinical utility without modification of these molecules that would reduce the rapid excretion (reviewed in von Itzstein et al, 1993a).…”
Section: Inhibition Of Assembly and Releasementioning
confidence: 99%
“…The lack of in vivo activity for FANA led to the generally accepted belief that potent synthetic analogues such as DANA would not have in vivo activity. In addition, subsequent work demonstrated that sialic acid analogues were rapidly excreted (Nohle et al, 1982), leading to the notion that DANA (Neu5Ac2en) analogues would not have potential clinical utility without modification of these molecules that would reduce the rapid excretion (reviewed in von Itzstein et al, 1993a).The elucidation of the X-ray crystallographic structure of influenza NA ushered in a new era of structure-based drug design for inhibitors of this enzyme. Early work that showed the HA and NA activities of influenza virus resided in two morphologically distinct surface 'spikes' (Laver & Valentine, 1969) Colman, 1991).…”
mentioning
confidence: 99%
“…Neu2enSGc was prepared in analogy to the synthesis of Neu2en5Ac as reported by Nohle et al [16]. To this end Neu5Gc was converted into the penta-0-p-nitrobcn7oyl derivative of its methyl ester.…”
Section: Preparation Of 2-denxy-23-didehydro-~-gly~~olnylnei~ramini~mentioning
confidence: 99%